054 Insight on the Intracrinology of Menopause: Androgen Production within the Human Vagina. (1st May 2022) - Comeglio, P.; Maseroli, E.; Cellai, I.; Di Stasi, V.; Todisco, T.; Filippi, S.; Sorbi, F.; Fambrini, M.; Petraglia, F.; Scavello, I.; Rastrelli, G.; Villanelli, F.; et al.
ABSTRACT: Introduction: The human vagina is extremely sensitive to hormonal changes occurring during the woman's lifetime, in particular the decline in estrogens that characterizes the menopause is known to induce a range of genital and sexual symptoms (dryness, burning, irritation, lack of lubrication, discomfort, pain), known as "genitourinary syndrome of menopause" (GSM). However, this reduction in estrogen levels is also accompanied by a progressive ageing-dependent decline in androgens for which the role of androgens in the development and treatment of GSM has received more attention. It is known that peripheral tissues compensate for circulating hormonal imbalances through the in-situ production of small quantities of sex hormones deriving from inactive precursors metabolized by specific cellular enzymes. This non-classical production and local activity of hormones is defined as "intracrinology". Objective: The aim of the study was to investigate whether the human vagina possesses the specific enzymatic machinery to convert weak androgen precursors, such as DHEA, into active androgens [Δ4-androstenedione (A), testosterone (T) and dihydrotestosterone (DHT)] as already described in other species. Methods: In this study, a well established model of human smooth muscle cells (hSMCs), isolated from vagina tissues of women undergoing surgery for benign gynecological diseases, was used. Semi-quantitative RT-PCR was employed in order to evaluate the mRNA expression of the steroidogenic markers in hSMCs and corrispective tissue. The production of androgens was quantified in hSMCs medium by liquid chromatography tandem-mass spectrometry (LC-MS/MS). Results: In vaginal tissues, AR mRNA was significantly less expressed than estrogen receptor α (ERα), whereas in hvSMCs, its mRNA expression was higher than progestin and both estrogen receptors. In hvSMCs and in vaginal tissue, when compared to ovaries, the mRNA expression of pro-androgenic steroidogenic enzymes (HSD3β1/β2, HSD17β3/β5), along with 5α-reductase isoforms and sulfo-transferase, resulted as being more abundant. In addition, enzymes involved in androgen inactivation were less expressed than in the ovaries. The LC-MS/MS analysis revealed that, in hvSMCs, short term DHEA supplementation increased Δ4-androstenedione levels in spent medium, while increasing testosterone (T) and dihydrotestosterone (DHT) secretion after longer incubation. Finally, androgenic signaling activation was evaluated through AR-dependent marker mRNA expression, after DHEA and T stimulation. Conclusions: This study provides evidence for the presence of steroidogenic machinery in the human vagina, supporting, for the first time, the construct of intracrinology in this organ, emphasizing that the vagina is an androgen-dependent organ. These observations suggest the potential mechanism and resulting action of intravaginally administered DHEA, recently indicated for the treatment of GSM and open new perspectives for the treatment of this common and bothersome condition. Disclosure: Work supported by industry: no.